67.5k views
2 votes
Give the standard form of the given equation below. If it is a quadratic equation, then give the a, b, and c coefficients. 3x2-2x-5x(x-7)=(x-2)(x+4)+1

Give the standard form of the given equation below. If it is a quadratic equation-example-1
User Geneise
by
4.9k points

1 Answer

7 votes

Answer:


\begin{gathered} -3x^2+31x+7=0 \\ a=-3 \\ b=31 \\ c=7 \end{gathered}

Explanation:

The quadratic equation in standard form is represented by:


ax^2+bx+c=0

For the following equation;


\begin{gathered} 3x^2-2x-5x(x-7)=(x-2)(x+4)+1 \\ 3x^2-2x-5x^2+35x=x^2+4x-2x-8+1 \\ -2x^2-2x+35x=x^2+2x-7 \end{gathered}

Compute all the terms on the left side, equalizing 0:


\begin{gathered} -3x^2+31x+7=0 \\ \text{Then, the a,b and c coefficeints would be:} \\ a=-3 \\ b=31 \\ c=7 \end{gathered}

User Fmodos
by
4.9k points